Role of Dendritic Cells in Inflammation and Loss of Tolerance in the Elderly - Agrawal, Anshu; Agrawal, Sudhanshu; Gupta, Sudhir (Frontiers in Immunology, 2017)
Dendritic cells (DCs) play an important role in advancing age-associated progressive decline in adaptive immune responses, loss of tolerance, and development of chronic inflammation. In aged humans, DCs secrete increased levels of pro-inflammatory cytokines and decreased levels of anti-inflammatory and immune-regulatory cytokines. This may contribute to both chronic inflammation and loss of tolerance in aging. Aged DCs also display increased immune response against self-antigens contributing further to both inflammation and loss of tolerance. The secretion of innate protective cytokines such as Type I and III interferons is decreased, and the function of DCs in airway remodeling and inflammation in aged is also compromised. Furthermore, the capacity of DCs to prime T cell responses also seems to be affected. Collectively, these changes in DC functions contribute to the immune dysfunction and inflammation in the elderly. This review only focuses on age-associated changes in DC function in humans.